An observation on bisection software for the symmetric tridiagonal eigenvalue problem. - Kaufman, Linda
In this article we discuss a small modification of the bisection routines in EISPACK and LAPACK for finding a few of the eigenvalues of a symmetric tridiagonal matrix A. When the principal minors of the matrix A yield good approximations to the desired eigenvalues, these modifications can yield about 30% reduction in the computation times.
Keywords: Bisection; Eigenvalues